2002
DOI: 10.1111/j.1530-0277.2002.tb02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Alcohol Exposure Affects Sperm Cytosine Methyltransferase Messenger RNA Levels

Abstract: Alcohol-induced reductions in cytosine methyltransferase mRNA levels may reflect altered genomic imprinting caused by reduced DNA methylation, which, in turn, may lead to the expression of normally silent paternal alleles and may be a mechanism for paternal alcohol effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(44 citation statements)
references
References 24 publications
6
38
0
Order By: Relevance
“…They are, however, in contrast with another study which indicated that ethanol exposure resulted in an increased DNMT activity as well as hyper methylation and decreased expression of cell cycle genes in neural stem cells (NSCs) [60]. Despite this observation, and consistent with our data, the Dnmt-1 transcript was down-regulated by alcohol in both neural stem cells [60] and rat sperm [61]. Numerous studies have reported the effects of ethanol exposure on gene expression [29,6269].…”
Section: Discussionsupporting
confidence: 79%
“…They are, however, in contrast with another study which indicated that ethanol exposure resulted in an increased DNMT activity as well as hyper methylation and decreased expression of cell cycle genes in neural stem cells (NSCs) [60]. Despite this observation, and consistent with our data, the Dnmt-1 transcript was down-regulated by alcohol in both neural stem cells [60] and rat sperm [61]. Numerous studies have reported the effects of ethanol exposure on gene expression [29,6269].…”
Section: Discussionsupporting
confidence: 79%
“…As discussed in Section 4, alcohol is known to affect methylation machinery, leading to severe health consequences, such as cancer (Varela-Rey et al, 2013). Particularly, alcohol has been shown to decrease activity of DNMT1 in somatic tissue (Ponomarev et al, 2012) and reduce cytosine methyltransferase mRNA in sperm (Bielawski, Zaher, Svinarich, & Abel, 2002). Alcohol is also known to reduce levels of the methyl donor SAM, leading to hypomethylation of somatic tissue (Lu & Mato, 2005).…”
Section: Possible Mechanisms For Germline-dependent Epigenetic Inhmentioning
confidence: 99%
“…A comprehensive list of the ethanol exposures used and primary findings of these studies is shown in Table 1. Several groups have found that paternal ethanol induces physiologic abnormalities in offspring in the absence of maternal ethanol exposure, including low birth weight (Bielawski, Zaher, Svinarich, & Abel, 2002; Ledig et al, 1998), increased number of runts (Bielawski & Abel, 1997; Bielawski et al, 2002), altered organ weights (Abel, 1993b; Ledig et al, 1998; Lee et al, 2013), thickening of layers of the cerebral cortex (Jamerson, Wulser, & Kimler, 2004), and low testosterone levels (Abel, 1989b). Several behavioral abnormalities have also been noted, including decreased spatiotemporal learning (Wozniak, Cicero, Kettinger, & Meyer, 1991), decreased novelty-seeking behavior (Ledig et al, 1998), increased immobility on the forced-swim test (Abel & Bilitzke, 1990; Liang et al, 2014), and decreased grooming (Abel, 1991a).…”
Section: Effects Of Paternal Ethanol Exposure On Offspringmentioning
confidence: 99%
“…Ethanol gavage 3 times per week for 9 weeks in rats was associated with decreased expression of the maintenance methyltransferase DNMT1 in sperm (Bielawski et al, 2002). Locus-specific studies have focused on the effect of ethanol consumption on DNA methylation at heavily methylated, imprinted regions in sperm that are resistant to genome-wide demethylation.…”
Section: How Does Ethanol Modify Heritable Variants In Germ Cells?mentioning
confidence: 99%